Determination of certain substances In electrotechnical products. Screening. Phthalates in polymers of electrotechnical products by high performance liquid chromatography with ultraviolet detector (HPLC-UV), thin layer chromatography (TLC) and thermal desorption mass spectrometry (TD-MS) Part 3-4, (15th June 2023) - British Standards Institution,
No abstract available